Penerapan Model Problem Based Learning: Analisis Tingkat Kemampuan Kognitif Individual Siswa Menggunakan Pendekatan Rasch Model - Anjani, Dewi Maulidah Nur; Sukarelawan, Moh. Irma (EDUKASI, 2024)
Analyzing students' individual cognitive ability levels has significant urgency in the context of modern education. Therefore, this study aims to analyse students' cognitive abilities using Rasch modelling. This research is a one-shot case study model on 23 students of class XI MIPA who took Thermodynamics material. Students' cognitive abilities were measured using 10 multiple choice questions after going through the problem-based learning (PBL) process. Students' cognitive ability data were analysed using Rasch modelling approach with a combination of Logit Value of Person (LVP) and Wright map techniques. Cognitive ability was assessed based on gender demographics. The results showed that female students tend to have higher cognitive abilities than male students in the context of thermodynamic problem solving. The implication of this research show that the application of the problem-based Learning (PBL) model can increase the effectiveness of physics learning and facilitate the development of students' critical thinking and analytical skills more optimally.